A comprehensive overview of the effects of probiotics, prebiotics and synbiotics on the gut-brain axis - Kezer, Gizem; Paramithiotis, Spiros; Khwaldia, Khaoula; Harahap, Iskandar Azmy; Čagalj, Martina; Šimat, Vida; Smaoui, Slim; Elfalleh, Walid; Ozogul, Fatih; Esatbeyoglu, Tuba (Frontiers in Microbiology, 2025)
The gut-brain axis (GBA) represents a complex bidirectional communication system connecting the gastrointestinal tract and the central nervous system through neural, endocrine, immune, and metabolic pathways. Emerging evidence suggests that dietary interventions, particularly probiotics, prebiotics, and synbiotics, can influence the composition and activity of the gut microbiota, thereby modulating GBA function. Such modulation has been linked to potential benefits for cognitive performance, emotional regulation, and resilience against neurodegenerative and neuropsychiatric disorders. In addition, these interventions may contribute to immune homeostasis and the management of chronic conditions such as inflammatory bowel disease, irritable bowel syndrome, and multiple sclerosis. Nevertheless, the mechanisms underlying these effects and their long-term clinical relevance remain incompletely understood. In this narrative review, we systematically synthesize current clinical and preclinical evidence on the role of probiotics, prebiotics, and synbiotics in regulating the GBA. Particular attention is given to their impact on neurocognitive outcomes and systemic health, highlighting both the therapeutic potential and the existing gaps that warrant further investigation.